The Thorny Side of Addiction: Adaptive Plasticity and Dendritic Spines - Patrick J. Mulholland; L. Judson Chandler (The Scientific World Journal)
Dendritic spines are morphologically specialized structures that receive the vast majority of central excitatory synaptic inputs. Studies have implicated changes in the size, shape, and number of dendritic spines in activity-dependent plasticity, and have further demonstrated that spine morphology is highly dependent on the dynamic organizational and scaffolding properties of its postsynaptic density (PSD). In vitro and in vivo models of experience-dependent plasticity have linked changes in the localization of glutamate receptors at the PSD with a molecular reorganization of the PSD and alterations in spine morphology. Chronic ethanol consumption results in adaptive changes in neuronal function that manifest as tolerance, physical dependence, and addiction. A potential mechanism supporting these adaptive changes that we recently identified is the homeostatic targeting of NR2B-containing NMDA receptors to the synapse. This increase is associated with and dependent on a corresponding increase in the localization of the scaffolding protein PSD-95 at the PSD, and with an actin-dependent increase in the size of dendritic spines. These observations led us to propose a molecular model for ethanol-induced plasticity at excitatory synapses in which increases in NR2B-containing NMDA receptors and PSD-95 at the PSD provide an expanded scaffolding platform for the recruitment and activation of signaling molecules that regulate spine actin dynamics, protein translation, and synaptic plasticity. This model is consistent with accumulating evidence that glutamatergic modulation of spine actin by the PSD plays a role in the aberrant plasticity of addiction.